On Commissioning New Music for Baroque Cello - Frey, Elinor (Circuit)

(untitled) (Circuit, musiques contemporaines, 2018)
In 2014, cellist Elinor Frey began commissioning new music for the five-string Baroque cello as a way to contribute to and expand the repertoire for the instrument. Her project grew to three new works for five-string cello, two works for the four-string cello, and one for cello and harpsichord. This article documents Frey’s close collaborations with six composers—Scott Godin, Isaiah Ceccarelli, Linda Catlin Smith, Maxime McKinley, Ken Ueno, and Lisa Streich—and reflects upon the ways in which her approaches to style and performance practice played a role in interpreting the new works. Frey also explores how she drew inspiration from Baroque stylistic qualities such as concealment and illusion.